Errors Found in Students' Theses: Capitalization, Punctuation, and Spelling - Putri, Nopa Ayu lia; Suhaimi, Suhaimi; Erniyati, Yelni (English Education Department at FKIP Nommensen University, 2024)
Writing is a skill that is considered difficult because many aspects must be considered. The aim of this research is to investigate and analyze the use of capitalization, punctuation, and spelling in the abstracts of theses. Understand the impact of these errors on written communication and provide concrete recommendations to enhance the quality of academic writing. This research was qualitative approach with text analysis, the population involves undergraduate students from English Department of IAIN KERINCI, and the sample was taken from the theses of the last 5 years, number of tenth theses on abstracts. Data was collected through manual analysis of thesis texts, focusing on capitalization, punctuation, and spelling. Based on the results of the researcher finding capitalization errors are the most prevalent, totaling 60 instances. On the other hand, punctuation errors, specifically in the abstract section of the theses, are comparatively lower, with only 25 occurrences. Meanwhile, spelling errors identified in the abstracts of the theses amount to 30 mistakes.